PENGARUH FEE DAN RELIGIUSITAS TERHADAP INDEPENDENSI DEWAN PENGAWAS SYARIAH DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE UNTUK MENINGKATKAN KINERJA BMT - Kholiq Hasan, Moh. Abdul; Prastiwi, Iin Emy; Triono, Dwi Condro (EQUILIBRIUM, 2017)
This article aims to determine the effect of fee and factor of religiosity on the independence of the Sharia Supervisory Board. It also aims to determine the influence the independence of the Sharia Supervisory Board and Good Corporate Governance individually or simultaneously on the performance of BMT in Sukoharjo and Karanganyar.This study used a sample of 30 data is spread over 9 BMT in Sukoharjo, and 6 BMT in Karanganyar. The hypothesis was tested using path analysis.The results in this study show fee and religiosity (practice) influence the independence of the Sharia Supervisory Board, the independence of the Sharia Supervisory Board and Good Corporate Governance partial and simultaneous influence on the performance of BMT.